2018
DOI: 10.1101/435057
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cannabichromene is a cannabinoid CB2 receptor agonist

Abstract: Running Title: Cannabichromene is a CB2 receptor agonist. BACKGROUNDCannabichromene (CBC) is one of the most abundant phytocannabinoids in Cannabis spp. It has modest anti-nociceptive and anti-inflammatory effects and potentiates some effects of Δ 9tetrahydrocannabinol (THC) in vivo. How CBC exerts these effects is poorly defined and there is little information about its efficacy at cannabinoid receptors. We sought to determine the functional activity of CBC at CB1 and CB2 receptors. EXPERIMENTAL APPROACHAtT20… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…CBC (0.001–1 μM) exhibited promising anti‐inflammatory effects in an in vitro model of colitis, decreasing LPS increased nitrite levels and attenuating IFN‐γ and IL‐10 secretion in peritoneal macrophages (Romano et al, 2013). More recently CBC acted as a CB 2 receptor agonist in AtT20 cells transfected with these receptors and was confirmed by application of the CB 2 receptor antagonist AM630, which blocked the effects of CBC (Udoh et al, 2019). We found only two papers related to neuroprotective effects of CBC; in vivo CBC suppressed motor activity while in vitro CBC improved viability of neural stem cells (Davis & Hatoum, 1983; Shinjyo & Di Marzo, 2013).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…CBC (0.001–1 μM) exhibited promising anti‐inflammatory effects in an in vitro model of colitis, decreasing LPS increased nitrite levels and attenuating IFN‐γ and IL‐10 secretion in peritoneal macrophages (Romano et al, 2013). More recently CBC acted as a CB 2 receptor agonist in AtT20 cells transfected with these receptors and was confirmed by application of the CB 2 receptor antagonist AM630, which blocked the effects of CBC (Udoh et al, 2019). We found only two papers related to neuroprotective effects of CBC; in vivo CBC suppressed motor activity while in vitro CBC improved viability of neural stem cells (Davis & Hatoum, 1983; Shinjyo & Di Marzo, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…Cannabichromene (CBC) was first isolated in 1966 by Gaoni and Mechoulam and is a non‐psychotropic cannabinoid that does not interact with CB 1 receptors (Gaoni & Mechoulam, 1966). CBC is an agonist at CB 2 receptors and TRP channels, acting potently at TRPA1 as well as displaying some activity at TRPV3 and TRPV4 channels (Cascio & Pertwee, 2015; De Petrocellis et al, 2008, 2011; de Petrocellis et al, 2012; Udoh, Santiago, Devenish, McGregor, & Connor, 2019). CBC (0.001–1 μM) exhibited promising anti‐inflammatory effects in an in vitro model of colitis, decreasing LPS increased nitrite levels and attenuating IFN‐γ and IL‐10 secretion in peritoneal macrophages (Romano et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have observed weak partial agonism of CBC at both CB1R and CB2R 8 . More recently, Udoh et al 50 reported that CBC produced CB2R-dependent membrane hyperpolarization in AtT20 cells. This effect was absent in CB1R-expressing AtT20 cells, indicating CB2R-specificity for CBC 50 .…”
Section: Discussionmentioning
confidence: 98%
“…The rationale for selecting the CBD and Δ 9 -THC compound families as independent variables lies in their relative abundance because total CBD and Δ 9 -THC concentrations in the cannabis plant are generally many times higher than those of other phytocannabinoids [ 41 ] and are, thus, thought to be the primary determinants of cannabinoid receptors activities. However, complex natural products such as cannabis can contain up to hundreds of unique compounds, and it remains unknown how less abundant phytocannabinoids, such as cannabichromene (CBC) and cannabigerol (CBG), affect the activity of cannabis extracts at cannabinoid receptors [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%